2007
DOI: 10.1097/psy.0b013e3180314b59
|View full text |Cite
|
Sign up to set email alerts
|

Outcome and Impact of Mental Disorders in Primary Care at 5 years

Abstract: Mental disorders are common and their recognition and treatment remain low. Subthreshold disorders have a better prognosis. Patients with threshold or multiple disorders, worse functioning or persistence of their disorder were more likely to be diagnosed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
51
1
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 57 publications
1
51
1
2
Order By: Relevance
“…It is likely that diagnostic accuracy will vary according to the number of contacts. Few studies have been designed to account for this [20,78,79]. In the studies of late-life depression that examined cumulative rather than cross-sectional detection over 6 [35,80] or 12 months [81], there was no appreciable additional effect on recognition, although the data were limited.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that diagnostic accuracy will vary according to the number of contacts. Few studies have been designed to account for this [20,78,79]. In the studies of late-life depression that examined cumulative rather than cross-sectional detection over 6 [35,80] or 12 months [81], there was no appreciable additional effect on recognition, although the data were limited.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Although primary care physicians account for most mental health visits and write the bulk of antidepressant and antianxiety…”
Section: Introductionmentioning
confidence: 99%
“…Other one-year follow-up studies of patients who screened positive for depression have had similar results (4245). Adverse outcomes among patients who screen positive for depression have been documented in a 45-month follow-up study of older primary care patients (20), a five-year follow-up study at Walter Reed Army Medical Center (24), and a seven-year follow-up study from Finland (25). However, some short-term follow-up studies of six to 12 months have reported that undetected mild depression resolves without intervention (20).…”
Section: Discussionmentioning
confidence: 99%